«Історія Русі-України має відношення до московської не більше, ніж історія Англії до історії США». Проекти програм з рідної історії для народних шкіл Харкова на 1942–1943 навчальний рік - Салтан, Н.; Салтан, О. (Сiверянський лiтопис, 2019)
У статті досліджується процес розробки шкільних навчальних програм з історії
України для народних шкіл Харкова часів нацистської окупації. Проаналізовано специфіку тем та методичних настанов, у контексті яких учителі мали інформувати
учнів щодо історичної минувшини рідної батьківщини. Виявлено антирадянські та
германофільські тенденції, які, у поєднанні з елементами українського патріотизму,
мали становити навчально-методичний комплекс засвоєння історичних знань підростаючим поколінням, що мало жити на теренах Третього Рейху.
Слід зазначити, що структура тем, зазначених у програмах, є авторським баченням низки тогочасних харківських істориків, важливе місце серед яких належить
чернігівцю Василю Дубровському. Саме він, на думку авторів, і став їхнім головним
розробником та упорядником.
Автори дійшли висновку, що (незважаючи на декларативний характер) створена
Василем Дубровським тогочасна модерна навчальна парадигма з історії України мала
сприяти поступовій трансформації світогляду школярів та закладала підвалини
нової системи цінностей на тлі видозміни історичної самосвідомості юних українців. The article explores the process of developing school curricula on the history of Ukraine
for the folk schools of Kharkiv, the times of the Nazi occupation. The specificity of topics and
methodological recommendations, in the context of which teachers should inform students
about the historical past of their homeland, is analyzed.
Anti-Soviet and germanophile tendencies were revealed which, in combination with
elements of ukrainian patriotism, constituted the educational and methodical complex of
mastering historical knowledge by the growing generation that was to live on the territory
of the Third Reich.
It should be noted that the structure of the themes indicated in the programs is the
author’s vision of a number of Kharkiv historians of that time, an important place among
which belongs to Chernihiv citizen Vasil Dubrovsky. It was he, according to the authors,
and became their main developer and compiler. Curricula were written in the light of the
political and ideological realities of that time.
So, immitating the German yudophobic and anti-communist sentiments, professor V.
Dubrovskii accused Jews and Bolsheviks of involvement in the exploitation and destruction
of the Ukrainian people in an explanatory note. Therefore, it is not surprising that during the
occupation students were given the opportunity to get acquainted with the true heroes of
the past of their people. Such a rethinking of their own history was to form national-patriotic
qualities of a sense of ethnic dignity eaten by communist ideologues of the 1920s – 1930s.
The authors came to the conclusion that (despite the declarative nature), the then modern
educational paradigm for the history of Ukraine, created by Vasul Dubrovskiy, was designed
to contribute to the gradual transformation of the world outlook of schoolchildren, laying
the foundations of a new value system against the background of a change in the historical
self-awareness of young ukrainians.